2015
DOI: 10.1136/bjophthalmol-2014-306331
|View full text |Cite
|
Sign up to set email alerts
|

Applicability of ISNT and IST rules to the retinal nerve fibre layer using spectral domain optical coherence tomography in early glaucoma

Abstract: Even though useful during ophthalmoscopy, ISNT and IST rules by themselves don't clearly distinguish normal eyes from those with glaucoma when applied to the quadrant values on RNFL on SD-OCT examination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
25
2
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(31 citation statements)
references
References 29 publications
3
25
2
1
Order By: Relevance
“…When previous histologic studies 10, 11 and OCT studies 16, 27 also used mean quadrant RNFL thickness values, they also demonstrated that the ISNT rule was valid (Table 1). However, when examining individual patients, we found that only 43.8% of subjects in our normal population met the ISNT rule (Table 2), which is similar to reported rates of 42% to 55%.…”
Section: Discussionmentioning
confidence: 90%
See 4 more Smart Citations
“…When previous histologic studies 10, 11 and OCT studies 16, 27 also used mean quadrant RNFL thickness values, they also demonstrated that the ISNT rule was valid (Table 1). However, when examining individual patients, we found that only 43.8% of subjects in our normal population met the ISNT rule (Table 2), which is similar to reported rates of 42% to 55%.…”
Section: Discussionmentioning
confidence: 90%
“…However, when examining individual patients, we found that only 43.8% of subjects in our normal population met the ISNT rule (Table 2), which is similar to reported rates of 42% to 55%. 16, 17, 27 This highlights that when applying a rule to an aggregate population, the rule may no longer be valid for the individual due to individual variability. In contrast to our findings for disc photos, we found that the sole reason that nasal RNFL thickness deviated from the ISNT rule was that the nasal quadrant was thinner than the temporal quadrant in 42.9% of normal subjects (Figure 4), which was a surprising finding and not previously reported by other studies.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations